Komunikasi dan Konflik Antarorganisasi - Damanik, Elsye Rumondang (Humaniora, 2013)
Conflict may take place in interpersonal, group, and organizational level. In the organizational level, conflict very often influences the organization performance. In the case of interorganizational conflict, Apple and Samsung experienced the open-to-public conflict when Apple filed Samsung on rights violation charges. The purpose of this study is to discuss the role of communication in coping with organizational conflict. Qualitative research method is applied to analyze research problem.  Data are obtained from academic journal, and case study published in media. The data are descriptively prepared. This research used the dispute on rights violation between Apple and Samsung in 2012 as the case study. In order to focus on the problem, the case study is discussed using interorganizational conflict and organization change concepts. The analysis resulted on the idea that interorganizational conflict may bring negative and positive impacts to the organization. The conflict may potentially exist when two producers who manufactured identical product variants with different brand dispute innovation exclusive rights. The discussion concluded that conflict is the way organization interact with its environment, learn, and develop. Communication can be used to resolve the conflict.